2002
DOI: 10.1039/b110105f
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase microextraction of protein-bound drugs under non-equilibrium conditions

Abstract: Recently, we introduced an inexpensive and disposable hollow fiber-based device for liquid-phase microextraction (LPME) where ionic analytes typically were extracted and preconcentrated from 1-4 mL aqueous samples (such as plasma and urine) through an organic solvent immobilized in the pores of a polypropylene hollow fiber and into a 10-25 microL volume of acceptor phase present inside the lumen of the hollow fiber. Subsequently, the acceptor phase was directly subjected to the final analysis by a chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 16 publications
0
39
0
3
Order By: Relevance
“…Thus, the recovery values reported may be improved by further method optimization. Extraction times of 60 min were selected in this fundamental work to present equilibrium data; however, a recent publication has shown that rapid LPME may be carried out under nonequilibrium conditions with only slightly reduced recovery and with no performance reduction with respect to validation parameters [13].…”
Section: Selection Of Drugs and Extraction Conditions For Three-phasementioning
confidence: 99%
“…Thus, the recovery values reported may be improved by further method optimization. Extraction times of 60 min were selected in this fundamental work to present equilibrium data; however, a recent publication has shown that rapid LPME may be carried out under nonequilibrium conditions with only slightly reduced recovery and with no performance reduction with respect to validation parameters [13].…”
Section: Selection Of Drugs and Extraction Conditions For Three-phasementioning
confidence: 99%
“…Normally, extraction time range between 15 and 45 min for sample volumes below 2 mL, whereas for 1 L samples even 2 h may be required to reach equilibrium (Pedersen-Bjergaard & Rasmussen, 2008). Recently, some proposals have been made in order to speed up the throughput of the procedure, either by treating many samples in parallel, carrying out the extraction under non-equilibrium condition (Ho et al 2002), or using the so called dynamic hollow fiber protected liquid phase microextraction (DHFP-LPME). The latter technique was successful applied by Huang & Huang (2006) in the extraction of OCPs from green tea leaves and ready-to-drink tea prior to GC-ECD analysis.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Neste sentido, Ho et al 51 estudaram o efeito de diferentes estratégias para supressão destas interações e observaram que, dependendo das características do analito, a adição de metanol em diferentes proporções pode ser útil. Outros trabalhos envolvendo a análise de fármacos no plasma são descritos na literatura (Tabela 1).…”
Section: Plasmaunclassified